Analisis Usability Website Keluarga Besar Mahasiswa Sistem Informasi Universitas Brawijaya menggunakan Usability Testing - Riski Adam Elimade; Retno Indah Rokhmawati; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Student Family Information System (KBMSI) is an organization formed from Student Information System Universitas Brawijaya. KBMSI also use the website as a medium to meet the information needs for the outside community as well as students of their own Information Systems, especially for Information System students themselves. With the website KBMSI expected society and student Information Systems get ease when looking for information about KBMSI. But it still needs to be considered by looking at the level of Usability on the website of the Student Family Information System (KBMSI). One technique to find out if the website is easy to use is by testing Usability. Usability is a quality that the product or service has about the level of convenience that the service user can do whatever it wants to do in the way it is expected to do. Based on interviews and observations made by the author, found some problems that exist in the website of the Student Family Information System (KBMSI). Based on the interview also found some empty website content. This will affect the user's expectation of the content. Website Family Student Information System (KBMSI). According to Michael O. Leavitt and Ben Shneiderman (2003) in his book Research-Based Web Design & Usability Guidelines, the website format must be ensured to meet user expectations, especially with regard to navigation, content and organization. the information presented in the website has not met the expectations of users.